A Self-Evaluation of Pre-School Education Institutions with an Emphasis on the Level of Their Inclusivity - Šilonová, Viera; Klein, Vladimír; Rochovská, Ivana (Special Education, 2024)
The issue of inclusive education, on the theoretical and empirical level currently within pedagogy (and not only within it), belongs to an extremely topical and discussed theme. In a humanistic oriented society, it is necessary to promote a philosophy of education that emphasises education for everyone without distinction and without exclusion, so that diversity becomes the norm. Subsequently, it is possible to divide children not institutionally but in terms of content, i.e. to manage processes in a direction away from segregated special schools towards inclusive kindergartens and primary schools and to strive for the personal growth of each child without any comparison with other children.The Index for Inclusion was defined by a British organisation called the Centre for Research on Inclusive Education and the Inclusivity Index published within it, which defines inclusive education in the form of the steps needed to better translate it into practice (Booth et al., 2004, 2006). In its essence, it is a self-assessment tool designed for schools, but also for public institutions.The Index for Inclusion consists of four basic pillars: Inclusion is a process – it is a never-ending process of finding individual and systemic answers to the ever-changing diversity within society and in schools. Inclusion is related to the identification and removal of barriers – the ability to identify barriers requires the collection, compilation and evaluation of comprehensive data from a variety of sources to improve policy and praxis. Inclusion means the presence, participation, success and happiness of all children – success is associated with the outcomes of the educational process, which go beyond the framework of the testing of knowledge. Inclusion includes special attention to those target groups which face the threat of the marginalisation, exclusion and achievement of the below average in education (Booth & Ainscow, 2016).The research is focused on the creation of a self-evaluation tool for determining the level of inclusivity of kindergartens and its verification in praxis. The purpose of self-assessment is to raise existing standards for a more effective upbringing and education. Effective kindergartens should constantly re-evaluate their own praxis and look for ways which will contribute towards improving the quality of the kindergarten, with an emphasis on its inclusivity. It is necessary to realise that there is a direct relationship between professional development and the self-evaluation of the school. The self-evaluation of pedagogical and professional employees of kindergartens contributes to their self-knowledge, self-reflection and self-criticism, based on their own performance and professional development. In this context, the research focuses on creating a model of school self-assessment which will allow kindergartens to evaluate their own inclusive educational practices. The self-evaluation questionnaire is part of the Methodical Manual of Inclusive Pre-primary Education (Šilonová & Klein, 2020) and is based on an individual analysis and evaluation, requires subsequent consultation and confrontation of opinions, and a search for consensus, thus promoting mutual communication in areas requiring further improvement and development. It is necessary to discuss proposals and plans on how to improve education in these areas.In the intentions of the presented knowledge and possible starting points relevant to the given research, a research problem was formulated: Will the application of the developed self-evaluation tool contribute towards increasing the inclusivity of kindergartens in the areas of culture, policy and praxis?The aim of the research was to verify the Index for Inclusion of kindergartens within selected localities through their self-evaluation. It can be assumed that the results from the output self-evaluation of kindergartens from the “Rest of Slovakia” region will be statistically significantly better than the results from the input self-evaluation of pre kindergartens from the “Rest of Slovakia” region. It can also be assumed that the results from the output self-evaluation of kindergartens from the Prešov region will be statistically significantly better than the results from the input self-evaluation of kindergartens from the Prešov region. It can also be assumed that the results from the output self-evaluation of kindergartens from the Košice region will be statistically significantly better than the results from the input self-evaluation of kindergartens from the Košice region.The self-evaluation tool for kindergartens consists of three main areas of the Index for Inclusion: culture, policy and praxis. In the area of culture, the following items were monitored: Kindergarten Climate, Cooperation of the Kindergarten with Parents, the School Authority and the Community, Internal and External Communication. In the area of policy, the following items were monitored: Objectives and Plans of the Kindergarten, Decision Making Processes, Personal Development, Spatial and Material-Technical Conditions., School Education Program. In the field of praxis, the following items were monitored: Achieved Results within an Inclusive Education, Education, Learning, Education of Children with Special Educational Needs.In total, 115 kindergartens (762 respondents) participated in the input self-evaluation within the framework of the National PRIM project and 96 kindergartens (559 respondents) participated in the output self-evaluation. From the total number of 115 kindergartens involved, 42 kindergartens from three areas of the Slovak Republic were selected by proportional stratified selection (according to the criterion of the number of pedagogical and professional employees): (1) Košice Region (KE) – 14 kindergartens; (2) Prešov Region (PO) – 14 kindergartens; (3) Rest of Slovakia (RS) – 14 kindergartens (Žilina region, Banská Bystrica region, Trenčín region and Nitra region).To verify the hypotheses for items where there was more than a binary scoring, a paired t-test was used, as the two groups of measurements were based upon the same sample of respondents who were tested twice (input and output measurements) and these were compared to each other. By subtracting the second measurement from the first for each subject, pairwise differences were obtained and entered into the analysis.Based on the research findings, it can be stated that the results from the output self-evaluation of kindergartens from the “Rest of Slovakia” region were statistically significantly better than the results from the input self-evaluation of pre kindergartens from the “Rest of Slovakia” region. The results from the output self-evaluation of kindergartens from the Prešov region were not statistically significantly better than the results from the input self-evaluation of kindergartens from the Prešov region. The results from the output self-evaluation of kindergartens from the Košice region were not statistically significantly better than the results from the input self-evaluation of kindergartens from the Košice region.The created questionnaire can be a valuable and effective tool for measuring the Index for Inclusion in the environment of kindergartens. Its application will make it possible to obtain useful feedback from the entire school community, which will contribute to the development of the upbringing and education of all children.The research is published as part of VEGA project No. 1/0114/23 “Possibilities of inclusive education of students with special educational needs”.
Keywords: self-evaluation; inclusive education; Index for Inclusion; pre-school education institutions; pre-school education